Facile pathway to construct mesoporous silica nanoparticles loaded with pyraclostrobin: Physicochemical properties, antifungal activity, and biosafety. Issue 6 (23rd March 2022) - Feng, Jianguo; Chen, Zhiyang; Chen, Wang; Sun, Li; Yang, Jinghan; He, Kangli; Dong, Sa; Yuan, Shuzhong
Abstract: BACKGROUND: A controlled‐release formulation based on mesoporous silica nanoparticles (MSNs) provides an effective way for reducing pesticide use and protecting the ecological environment. In this study, MSNs loaded with pyraclostrobin (PYR@MSNs) were prepared using a one‐pot method. RESULTS: The characteristics of PYR@MSNs were systematically investigated, including morphology, loading content, ultraviolet (UV) resistance, release behavior, control effects against pathogens, and safety to nontarget organisms. The results show that the prepared PYR@MSNs presented characteristics of regular spherical shapes, uniform particle size (200 nm), high drug loading (38.9%), and enhanced UV resistance. Compared with traditional formulation, PYR@MSNs exhibited improved control effects against Fusarium graminearum, an extended control period, and lower toxicity to zebrafish, earthworms and BEAS‐2B cells. CONCLUSIONS: This research will facilitate the development of efficient and safe pesticide delivery systems. The PYR@MSNs has showed its potential as a new controlled‐release formulation with increased efficacy and is expected to benefit the sustainable development of agriculture. © 2022 Society of Chemical Industry. Abstract : Mesoporous silica nanoparticles loaded with pyraclostrobin (PYR@MSNs) were prepared by a one‐pot method. Compared with the traditional formulation, PYR@MSNs had improved control effect against Fusarium graminearum, an extended control period, and lower toxicity to zebrafish, earthworms and BEAS‐2B cells.